Evolution of the stereoselective pinacol coupling reaction - Chatterjee, A.; Joshi, Navalkishore N. (Tetrahedron, 2006)
Keywords: diastereoselective; enantioselective.; pinacol coupling; reductive dimerization

Preparation of enantiopure trans-1,2-cyclohexanediol and trans-2-aminocyclohexanol - Chatterjee, A.; Sasikumar, M.; Joshi, Navalkishore N. (Synthetic Communications, 2007)
Trans-1,2-cyclohexanediol and trans-2-aminocycloxexanol are useful chiral auxiliaries. Simple chemical resolution procedures for these molecules are presented.
Keywords: chemical resolution; chiral auxiliaries; epoxide-cleavage